Dinâmica da serrapilheira de taxa de decomposição de resíduos culturais - Silva, Antonio Sousa (2012)
The difficulty of implementing no tillage in the Northeast region of Brazil occurs due to low rainfall, which limits the plant growth and high rates of decomposition. In the Brejo Paraibano microregion, beyond this aspect, another problem is related to changes in the use of soil, without considering their potentialities and limitations, which provided serious damage to conservation. In order to select cover crops for no tillage and understand the soil degradation due to changes in use, was implanted two experiments completely randomized. The experiment of cultural residues was conducted in the Chã of Jardim farm, of Center of Agrarian Sciences of UFPB, and the treatments consisted of three residues of grass species (Brachiaria decumbens), corn (Zea mays) and sorghum (Sorghum bicolor) and three legumes species: pigeon pea (Canavalia ensiformis), guandu (Cajanus cajan) and leucena (Leucaena leucocephala). The residues were placed in litter bags and placed in the experimental field under the litter, in the presence and absence of nitrogen. The experiment about use of soil was conduced in three systems: native secondary forest, cultivation of sabiá (Mimosa caesalpiniaefolia) and pasture (Brachiaria decumbens). In each area, soil samples were collected at four depths for physical and chemical analisys, fractionation of organic matter and root density. The physical analisys consisted of the separation of aggregates size, grain size, density and total porosity of soil. The chemical ones consisted of determining the pH and concentration of calcium, magnesium, phosphorus, potassium, sodium, aluminum and C. The organic matter was fractionated into fulvic acid fraction (FAF), humic acid fraction (HAF) and humin (HUM). They were quantified deposition and accumulation of litter and its rate of decomposition in areas of woodland and thrush. In the pasture, one evaluated the production of forage. In the case of crop residues, it was observed that the rate of decomposition of the grass is slower than that of legumes, however, this rate is equivalent in the last months of the evaluated year. The grasses showed no differences, but the guandu showed slower rate of decomposition amongst the legumes. Nitrogen fertilization did not affect the waste decomposition rate. In the case of the changes in the use of the soil, the amount of clay, DMPAs, DMPAu and the relationship DMPAu / DMPAs and porosity showed higher values in the area under forest. xi The soil density was lower in the area under forest. The development of roots was higher in areas under forest and pasture. The waste disposal was greater in the area under sabiá and the N, P and K were higher in these residues, which shows the sabiá capacity in nutrient cycling. The accumulation of litter in the soil was higher in the area under forest. The decomposition rate of the waste was 48% in area under sabiá and 40% in that one under forest. The percentage of C, H + Al, Al, and CTC potential and aluminum saturation (m) are higher in the soil in the area under forest. The soil pH, the base saturation (V) and the concentrations of Na and K are similar in areas under pasture and under sabiá and larger than that under forest. The percentages of Ca, Mg and available P and SB and effective CTC did not differ among the studied areas. The C of the soil is best preserved in the area under forest in function of higher levels in HAF and HUM fractions and the lowest ratio EA / HUM. In turn, the replacement from the grass for sabiá begins to recover the levels of C lost in the area under pasture, with intermediate fraction values of HAF and HUM, demonstrating the sabiá ability to recover soil quality.